2021
DOI: 10.1155/2021/6623706
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting BRAF-Mutated Langerhans Cell Histiocytosis and Primary Myelofibrosis with Shared JAK2 Mutation

Abstract: Langerhans cell histiocytosis (LCH) is an infrequent disease, characterized by oligoclonal proliferation of immature myeloid-derived cells. However, the exact pathogenesis remains unknown. In rare cases, LCH is present in patients with concomitant myeloid proliferative neoplasms. Here, we describe a 69-year-old male, who presented with a maculopapular rash covering truncus, face, and scalp. A cutaneous ulcerating lesion on the right cheek led to a biopsy showing LCH. Lesional cells were BRAFV600E and JAK2V617F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a review by Kemps PG et al (34), mutated genes in histiocytic disorders and myeloid neoplasms have been reported in 30 cases (29,. A total of 31 cases, including one additional case of a common mutation found in LCH and primary myelofibrosis (39), including the present case are shown in Table 2. There have been five cases, of LCH occurring concurrently with a myeloid neoplasm, including the present case.…”
Section: Discussionmentioning
confidence: 75%
“…In a review by Kemps PG et al (34), mutated genes in histiocytic disorders and myeloid neoplasms have been reported in 30 cases (29,. A total of 31 cases, including one additional case of a common mutation found in LCH and primary myelofibrosis (39), including the present case are shown in Table 2. There have been five cases, of LCH occurring concurrently with a myeloid neoplasm, including the present case.…”
Section: Discussionmentioning
confidence: 75%
“…However, we could not have access to seven papers written in Japanese that were cited in one record 19 . Therefore, our study included 43 papers, describing 47 patients 6,9,19–59 …”
Section: Resultsmentioning
confidence: 99%
“…Histopathologically, the skin lesions revealed a picture of EMH in most cases (76.6%) and less frequently leukemic blast infiltration (LC, 12.8%), cutaneous involvement of Langerhans cell histiocytosis (LCH, 6.4%), 55,57,58 reticulohistiocytosis (2.1%), 42 or histiocytoid Sweet syndrome (2.1%) 12 . Cutaneous EMH lesions were described as dermal infiltrates composed of cells of the three hematopoietic lineages, in different stages of maturation, with occasional mitoses, megakaryocytic atypia (mononucleation, nuclear hyperchromasia, dysmorphism, and small cell size), and dermal fibrosis 6,19,34,44 .…”
Section: Resultsmentioning
confidence: 99%